Functional Role of Lacrimal Gland Fibroblasts in a Mouse Model of Chronic Graft-Versus-Host Disease. Issue 1 (January 2018) - Yamane, Mio; Ogawa, Yoko; Mukai, Shin; Yaguchi, Saori; Kamijuku, Hajime; Inaba, Takaaki; Asai, Kazuki; Morikawa, Satoru; Kawakami, Yutaka; Shimmura, Shigeto; Tsubota, Kazuo
Abstract : Purpose: This study aimed to clarify the mechanisms and assess the characteristics of the chronic graft-versus-host disease (cGVHD) fibrosis in the lacrimal gland (LG) of mice. Methods: Histopathology of LG tissues was examined by immunohistochemistry and electron microscopy. Cultured fibroblasts derived from the LG were analyzed by phase-contrast microscopy, immunocytochemistry, flow cytometry, proliferation assay, and invasion and migration assays. Results: Cultured murine LG fibroblasts in cGVHD were spindle-shaped and relatively small, whereas those from syngeneic controls were polygon-shaped and relatively large. Flow cytometric analysis showed that the LG fibroblasts in cGVHD had elevated HSP47 levels. The LG fibroblasts in cGVHD also showed increased expression of major histocompatibility complex class II. Furthermore, the proportion of Sca-1 + PDGFR-α + cells among the LG fibroblasts in cGVHD was considerably increased compared with controls. Cell counting kit-8 assays demonstrated that the LG fibroblasts in cGVHD were highly proliferative, and cell invasion assays indicated that they were highly invasive with high migration ability. Conclusions: LG fibroblasts in cGVHD can be aberrantly activated, thereby eliciting fibrosis by producing excessive extracellular matrix, leading to LG dysfunction in mice.